Design A Lighting Point Calculator System For Residential Houses Using Microsoft Visual Basic - Fatin Farhah Nazaruddin; Mohammad Radzi, Nur Hanis (Journal of Electronic Voltage and Application, 2021)
Lighting point calculation plays an important feature in developing a new residential house. This enables people inside the house will have enough of light to perform tasks efficiently. Currently, consulting electrical engineers use rules of thumb to forecast the quantity of lighting points, however these rules are inaccurate. It does not take into account the lux required based on Malaysian Standard MS1525. Furthermore, good lighting can save money and provide visual comfort to the occupants. However, numerous parameters such as room index, utilisation factor and illuminance used for each space or room inside the house must be considered when determining the quantity of lighting point for a residential property. Three types of residential houses are considered which are: single storey house, double storey house and condominium house. This paper presents the development of lighting point calculator system for residential houses using Microsoft Visual Basic and comparison of quantity of lighting point using manual calculation using Microsoft Excel and simulation calculation using Microsoft Visual Basic.